ANALYSIS OF THE USE OF ANIMATED VIDEO LEARNING MEDIA ON THE SCIENCE LEARNING MOTIVATION JUNIOR HIGH SCHOOL STUDENT - Ayunda, Yuanda; Azmi, Difa’ Isabitul; Suhartatik, Suhartatik (Jurnal Pembelajaran Sains, 2024)
Animated videos in learning can increase students' learning motivation. This study aims to analyze the impact of using animated video learning media on the science learning motivation of 8th-grade students in Nasional Junior High School Malang. The research employed a descriptive qualitative method with data collection techniques through questionnaires. The research subjects consisted of 32 students who participated in learning sessions using animated video media on the topic of the human organ system. The findings revealed that most students responded positively to the use of animated video media. Students felt more motivated, enthusiastic, and found it easier to understand the material compared to conventional teaching methods such as lectures. The combination of visual and audio elements in the animated videos successfully created a more interactive and enjoyable learning atmosphere, thus increasing students' interest and engagement in the learning process. Therefore, animated video media is recommended as an effective alternative learning tool to enhance students' learning motivation in science subjects.